Magmatic stratigraphy of the Tweespalk Section towards potential correlation with the other known Bushveld Complex sequences north of the Thabazimbi-Murchison Lineament - Marx, Daniel George (My University, 2021)
The northern limb of the Bushveld Complex forms part of one largest repositories of PGE-Ni-Cu in the world in the world. The limb has historically received significantly less attention when compared to the eastern and western limbs of the Bushveld, and until more recently has been left largely underexplored. The discovery of the now world-renowned Platreef sparked an increase in the economic potential of the area, with the heightened exploration focus on the limb resulting in the identification of a diverse array of mineralisation types and styles not accounted for in the Platreef definition (ss). This includes the Aurora and Waterberg deposits located further to the north of the observed Platreef extension. The Tweespalk property is situated towards the middle of the northern limb, within a ~10 km section between the Witrivier and Nonnenwerth properties. This section is notably depleted with regards to PGE or Ni-Cu sulphide mineralisation when compared to the high grades seen throughout the Platreef to the south, as well in both the Aurora and Waterberg projects further north. This study has shown that the magmatic stratigraphy at Tweespalk correlates with the conventional northern limb stratigraphy and is representative of both Upper and Main Zones. However, the presence of the local granite gneiss basement high that rises northwards, forms the northern edge of the basin and has resulted in the impeded development of the full Bushveld stratigraphy at Tweespalk. The succession shows an observed but discrete transition from predominantly MZ lithologies through to more felsic and magnetite-rich UZ lithologies, with the UZ-MZ boundary being placed at a depth of 566.1 m, which is ~24.9 m below the first cumulus magnetite-bearing unit. No specific marker horizon (troctolite or pyroxenite markers) was observed within the ~182.2 m MZ at Tweespalk, suggesting that the magmatic stratigraphy in the area comprises a small portion of upper MZ and a thick UZ portion above. In terms of mineralisation within the stratigraphy, the study highlights the absence of two major processes that typically enhance the likelihood of mineralisation within the stratigraphy. The first is the lack of contamination of the intruding magma as a result of limited interaction with the relatively impermeable Archaean granite gneiss basement. In contrast to northern limb stratigraphies that are underlain by various Transvaal Supergroup basement rocks, which contributed significantly towards the development of economic mineralisation. The second is the lack of evidence to support mixing between the new UZ magma influx and residual magma in the chamber during formation. The study concludes that the Tweespalk stratigraphy compares with the typical geology of the northern limb as well as the rest of the Bushveld Complex. The development of the full MZ and underlying RLS however, was inhibited by the local granite gneiss basement high which in turn led to lack of any significant economic mineralisation within the area
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Economic Geology at the School of Geosciences, University of the Witwatersrand, 2021